UTILITY OF CA 19-9 AND CEA IN DETERMINING RESECTABILITY OF PANCREATIC CANCER - Dr. Aklima Parvin; Dr. Sayem Al Monsur Faizi; Dr. Mohammed Rafiqul Islam; Dr. Md. Saiful Islam; Dr. Rana Jahangir Alam (Medico Research Chronicles, 2020)
Background: Pancreatic cancer considered as a ‘silent killer’ is usually diagnosed at the late stage of its course. Therefore, the accurate determination of its resectability is the most important contribution to reduce needless surgery to a minimum.Objective: The aim of the study was to assess the utility of serum CA 19-9, CEA in determining resectability of pancreatic cancer.Methods: This was a prospective observational study among purposively selected 54 patients diagnosed as pancreatic cancer in Dhaka Medical College Hospital (DMCH) from 1st July 2016 to 31st June   2017.  The patients were evaluated by history, physical examination and investigations. The patients were considered to have potentially resectable tumour after assessment. The patients were undergoing surgery for potential tumour resection at the operation theater. Statistical analyses of the results were be obtained by using window-based Microsoft Excel and Statistical Packages for Social Sciences.Results: This study shows 59.26% (32) patients were in >60 years age group. 62.96% (34) patients were male out of total 54 patients. 98.15% (53) patient had jaundice, 96.30% (52) had weight loss. There was no significant association between CA 19-9, CEA with age, sex and clinical features.  Out of the 54 patients, 45 patients were resectable pancreatic carcinoma and 9 patients was unresectable. In this study sensitivity was 88.9%, specificity was 55.6%, PPV was 90.9% and NPV was 50% for CA 19-9. In CEA, sensitivity 77.78%, specificity was 55.56%, PPV was 89.74% and NPV was 33.33%. Conclusion: The study revealed that lower level of CA 19-9 and CEA can be utilized to determine resectiablity in patients with pancreatic carcinoma with a good positive predictive value.